2009
DOI: 10.1007/s00449-009-0321-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of domestic wastewater in an up-flow anaerobic sludge blanket reactor followed by moving bed biofilm reactor

Abstract: The performance of a laboratory-scale sewage treatment system composed of an up-flow anaerobic sludge blanket (UASB) reactor and a moving bed biofilm reactor (MBBR) at a temperature of (22-35°C) was evaluated. The entire treatment system was operated at different hydraulic retention times (HRT's) of 13.3, 10 and 5.0 h. An overall reduction of 80-86% for COD total ; 51-73% for COD colloidal and 20-55% for COD soluble was found at a total HRT of 5-10 h, respectively. By prolonging the HRT to 13.3 h, the removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 34 publications
2
18
0
2
Order By: Relevance
“…[262] The main features of these reactors are the bacterial sludge immobilization inside the reactor. The most significant two-stage anaerobic reactors developed are the following: up flow anaerobic sludge blanket (UASB), [268,269] up flow and down flow anaerobic filters (UFAF, DFAF), anaerobic fluidized bed reactors (AFBR), [270,271] and anaerobic attached film expanded bed reactor (AAFEB). [272][273][274] Many industrial processes are running based on these technologies.…”
Section: Biomethane Via Biogasmentioning
confidence: 99%
“…[262] The main features of these reactors are the bacterial sludge immobilization inside the reactor. The most significant two-stage anaerobic reactors developed are the following: up flow anaerobic sludge blanket (UASB), [268,269] up flow and down flow anaerobic filters (UFAF, DFAF), anaerobic fluidized bed reactors (AFBR), [270,271] and anaerobic attached film expanded bed reactor (AAFEB). [272][273][274] Many industrial processes are running based on these technologies.…”
Section: Biomethane Via Biogasmentioning
confidence: 99%
“…Although MBBR provides a long biomass retention time and hold high loading rates without any problems of clogging (15). However, on the basis of results, it can be concluded that with an increase in OLR ammonia concentration in the final effluent (11,17) and COD will be an increase. As shown in figure 5, average MLSS concentration in conventional ASP generally was 1291.14 ± 463.43 mg/L for wastewater treatment, whereas in the MBBR process high removal efficiency was obtained even at a relatively low MLSS concentration (average MLSS in the water phase = 190.1 ± 29.80 mg/L).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, posttreatment of anaerobically treated wastewater is usually required in order to improve the quality of effluent in accordance with the irrigation standards. This has been successfully done by conventional systems such as maturation ponds, waste stabilization ponds, polishing ponds, constructed wetlands, rotating biological contactors, moving bed biofilm reactor, downflow hanging sponge [60][61][62], and advanced oxidative processes (AOPs) [63,64].…”
Section: Posttreatment Requirementsmentioning
confidence: 99%